2020
DOI: 10.1038/s41598-020-61623-w
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine growth restriction in piglets alters blood cell counts and impairs cytokine responses in peripheral mononuclear cells 24 days post-partum

Abstract: Large litter sizes have resulted in more piglets being exposed to intrauterine growth restriction (iUGR). Growth restriction during fetal life is linked with lower growth efficiency and increased susceptibility to infections in postnatal life and iUGR may associate with an altered innate immune system. We investigated the haematological, thromboelastography and plasma biochemical profiles of IUGR and normal piglets as well as cytokine responses in peripheral blood mononuclear cells stimulated with lipopolysacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 24 publications
3
36
0
Order By: Relevance
“…The relative abundances of these genera were subsequently correlated to all measured parameters in Amdi et al [ 24 ] (see Figure 7 ). We identified a significant correlation for a few parameters.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The relative abundances of these genera were subsequently correlated to all measured parameters in Amdi et al [ 24 ] (see Figure 7 ). We identified a significant correlation for a few parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Treponema was most abundant in the black feces and is a genera that is associated with infections in IUGR piglets [ 40 ], although it was not elevated in IUGR piglets in this study. To further support these results, no differences were found in the blood biochemistry between IUGR and normal piglets, for example, the albumin levels (34.9 g/L vs. 34.5 g/L; p = 0.796) and total protein levels (49.95 g/L vs. 47.65 g/L; p = 0.207) were similar in normal and IUGR pigs, respectively [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies even suggested that this impaired immune status may persist for years after birth with SGA (8,9). From animal studies, low birth weight following term birth has been correlated with negative long term effects on growth as well as systemic and gut immune functions (10)(11)(12)(13). The possible effects of being both premature and SGA on immune development and infection risks during the first few days of life, remain elusive.…”
Section: Introductionmentioning
confidence: 99%